Investigating the diversity and therapeutic potential of circulating and tissue-resident memory CD4+ T cells elicited in response to Staphylococcus aureus - Clegg, Jonah Thomas (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2024)
Staphylococcus aureus is one of the most important pathogens globally to which a vaccine would prove enormously valuable. Furthermore, S. aureus can colonize humans asymptomatically. Resultingly, S. aureus elicits pre-existing immune responses in healthy individuals. The impact of such immune responses on vaccine function or protective immunity is however, not well understood. This thesis aimed to provide a deep characterization of the pre-existing CD4+ T cell response in humans and additionally investigate the capability of skin-resident CD4+ T cells to mediate protective immunity during S. aureus infection in a murine model. An activation induced marker assay based on the co-expression of OX40 and CD137 was employed to select for S. aureus-specific CD4+ T cells from the blood of healthy subjects and single-cell mRNA sequencing (scRNA-seq) was applied to deeply phenotype these cells. Bioinformatic analysis revealed the presence of both effector and regulatory CD4+ T cell (Treg) phenotypes. The effector arm was characterized by an enrichment in the production of Th17-associated associated cytokines when compared against polyclonally-activated CD4+ T cells. This effect was further accentuated in skin-homing S. aureus-specific CD4+ T cells. S. aureus-specific Treg strongly expressed the immune checkpoint receptor TIGIT, which upon blocking of its activity through monoclonal antibody treatment, led to increased IL-1β production in response to S. aureus in vitro. These results reveal the presence of a suppressive S. aureus-specific CD4+ T population in the blood of healthy subjects that could be responsible for the blunting of immune responses in response to vaccination or infection. The kinetics of cellular infiltration were assessed in a murine model of S. aureus skin infection. Total non-neutrophil immune cell infiltration and persistence was measured via scRNA-seq over the course of infection. A population of CD4+ T cells expressing a genetic signature associated with tissue residency were discovered, which remained present 42 days post-infection. These cells were characterized as CD69+ and largely CD103+, further indicative of a tissue residency phenotype. During reinfection with S. aureus, skin-resident CD4+ T cells produced elevated levels of the effector cytokines IFN-γ and IL-17A. Furthermore, while protection to secondary S. aureus infection was unaffected by inhibiting the infiltration of circulating lymphocytes, it was abrogated upon depletion of skin-resident CD4+ T cells. These findings identify skin-resident CD4+ T cells as a potential correlate of protection and therefore vaccine target for the prevention of S. aureus infections. Overall, this project provides in-depth characterizations of the immune response to S. aureus revealing the important consequences of pre-existing immunity. In doing so, this thesis identifies separate arms of the immune system that could be inhibited and expanded to potentially increase the efficacy of future vaccines or immunotherapies.
APPROVED
Keywords: Staphylococcus aureus; CD4 T cells; Tissue-resident memory T cells; Regulatory T cells; Pre-existing immunity